Local and community governance for peace and development in Nepal - Vidyadhar Mallik (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
The end of the ten-year-long armed conflict between the Maoists and the government and the peace agreements of late 2006 brought widespread hope for a more inclusive and well-governed Nepal. However, six years later in early 2013, the failure to produce the promised new constitution and an alarming deterioration of governance have exhausted the hope of most Nepalis. In 2011/12 the author carried out a study to examine the contribution of local and community-level governance for promoting peace and development during Nepal's post-conflict transition and beyond. The study also examined in detail the performance of four donor-supported programmes for local governance, poverty alleviation and peace building. This book presents the findings of the study and provides many insights into the situation of chronic political instability and the possibilities for fostering good governance, peace and development in Nepal.
Keywords: 330; Governance; Sicherheit; Frieden und fragile Staaten; Regionalverwaltung; Kommunalverwaltung; Good Governance; Politische Instabilität; Entwicklung; Entwicklungsprojekt; Deutsch; Projektbewertung; Nepal